Peran Guru dalam Peningkatan Kemampuan Literasi Membaca Siswa Sekolah Dasar: Systematic Literature Review - Ami Devi Novrianti (Jurnal Ilmu Bahasa dan Pendidikan Guru Sekolah Dasar, 2026)
Reading literacy among Indonesian elementary school students remains a significant educational challenge due to low reading interest and the suboptimal implementation of literacy programs in schools. This study aims to describe the role of teachers in improving elementary students' reading literacy based on published research findings. The study employed a Systematic Literature Review (SLR) method by identifying, selecting, evaluating, and synthesizing relevant journal articles obtained from Google Scholar, Garuda, and SINTA according to predetermined inclusion and exclusion criteria. The findings indicate that teachers play strategic roles as facilitators, motivators, instructional planners, and promoters of literacy culture in schools. Various efforts, including reading habituation, the use of diverse learning media, the creation of supportive learning environments, the provision of appreciation, and collaboration with parents, contribute to improving students' reading interest. It can be concluded that the success of reading literacy improvement largely depends on teachers' active involvement in designing and implementing sustainable literacy activities. These findings provide practical implications for teachers and schools in strengthening literacy programs and serve as a reference for future studies on the implementation of reading literacy strategies in elementary education.